Projektiranje enoetažnih armiranobetonskih montažnih hal po novem Evrokodu 8 - Isaković, Tatjana (Gradbeni vestnik, 2025)
The accompanying article demonstrated that, in the seismic design of single-story precast reinforced concrete buildings, the key seismic response parameters, assessed by elastic and nonlinear analyses, can differ by more than a factor of two. This follow-up article delves into these discrepancies, providing a comprehensive analysis and establishing relationships between the critical response quantities. Using these derived relationships, a new force-based procedure for the seismic design of single-story precast reinforced concrete buildings is proposed, yielding results comparable to those from nonlinear analysis. This method effectively integrates the effective stiffness of the structure, the required strength/ductility, and second-order effects, while eliminating the need for iterative calculations typically required in the force-based approach when standard parameter values are used (e.g., 50% stiffness of the gross cross-section and a behaviour factor q=3).
Keywords: enoetažne armiranobetonske montažne hale; Evrokod 8 druge generacije; force-based design; nelinearna potresna analiza; nonlinear seismic analysis; projektiranje po metodi sil; projektiranje za vpliv potresne obtežbe; second generation of Eurocode 8; seismic design; single-story precast reinforced concrete buildings